The Role Of Religiosity As A Moderator Of Intentions To Visit Halal Tourism: A Study On Generation Z Muslims In Bengkulu - Imron Rosyadi; Levy Oktridarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the factors influencing the intentions of Generation Z Muslims in Bengkulu Province to visit halal tourism destinations. The variables examined include subjective norms, attitudes, perceived behavioral control, halal awareness, and religiosity as a moderating variable. The study employs a quantitative approach, with data collected through surveys of Generation Z Muslim respondents in Bengkulu Province. The analysis was conducted using Structural Equation Modeling (SEM). The findings indicate that subjective norms and attitudes significantly influence travel intentions. This research provides practical implications for tourism managers in Bengkulu to enhance the appeal of halal destinations by promoting religious values and improving Muslim-friendly facilities.